Answer:
6m+24
Step-by-step explanation:
basically you multiply m and 4 by six soooo
6 times m is 6x
6 times 4 is 24
soo
6m+24 is correct
can i have rainliest pleaseee:)b
<span>add 2/9x to both sides, if you do that you get 2/9x+y=3. If you want to simplify it multiply everything by the denominator, in this case, 9 so then you would have 2x+9y=27
Thank you for posting your question here at brainly. I hope the answer will help you. Feel free to ask more questions.
</span>
Answer:
See method below.
Step-by-step explanation:
m/n + n/3 = 2
2/m + n = 4
First eliminate the fractions by multiplying the first equation by 3n:-
3m + n^2 = 6n...........(1)
and the second equation by m:-
2 + mn = 4m..............(2)
Now we solve using substitution:-
From equation (2):-
4m - mn = 2
m = 2 / (4 - n)
Now substitute for m in equation (1):-
6/ (4 - n) + n^2 = 6n
6 + n^2(4 - n) = 6n(4 - n)
6 + 4n^2 - n^3 = 24n - 6n^2
n^3 - 10n^2 + 24n - 6 = 0
This will not factor so we could solve this using graphical software.
To find the values of the variable m we substitute the found values of n into one of the original equations and solve for m.
There are three unknowns in this problem. First, let's assign variables for these unknowns.
Let
x be the amount received by the first friend
y be the amount received by the second friend
z be the amount received by the third friend
Next, we formulate equations for the relationships
x = 4z
z = 4y
x + y + z = <span>$231,000
Solving simultaneously,
4(4y) + y + 4y = </span><span>$231,000
21y = </span><span>$231,000
y = $11,000
z = 4($11,000) = $44,000
x = 4($44,000) = $176,000</span>